If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*(3*x-5) = (3/4)*(2*x+3) // - (3/4)*(2*x+3)
(2/3)*(3*x-5)-((3/4)*(2*x+3)) = 0
(2/3)*(3*x-5)+(-3/4)*(2*x+3) = 0
2/3*(3*x-5)-3/4*(2*x+3) = 0
2/3*(3*x-5)-3/4*(2*x+3) = 0
1/2*x-67/12 = 0
1/2*x-67/12 = 0
1/2*x-67/12 = 0 // + 67/12
1/2*x = 67/12 // : 1/2
x = 67/12/1/2
x = 67/6
x = 67/6
| i=(100)(0.12)(2) | | -8/3k=32 | | 1/7+1/3 | | x-16/5=23/10 | | 5x-5=28-x | | 15y+8=16y | | 1=x+4/6 | | F(x)=-5x+7 | | p=2(29)+2(102) | | 5/8n=33/4 | | 20-2n=3n-10 | | 3x+5x=17 | | 10+4x=70 | | 4x-1/10 | | 63/8+14/3+73/4 | | 2(y-3)/5=3y | | 4x^2-3=125 | | 23-4x=23 | | 126-10x=2x | | 5x-3=35 | | m-2/9=40/9 | | m/10=9 | | x^2+1x-42= | | x+x+17+(3x-20)=662 | | 7/9b=31/9 | | 1/2(3y-1)+1/4(6y+5)= | | x^2+1-42=0 | | -18=r/4 | | x^3=26 | | X+1/x+2 | | -10x=170 | | (y^2/3) |